(untitled) (Jurnal Bahasa, 2024)
The development of metaphor studies has shown that various aspects have been explored, including research on metaphor interpretation procedures that focus on methods used by researchers to uncover implied meanings. Therefore, various metaphor interpretation procedures have emerged, proposed by scholars with their own characteristics and methods. This paper highlights the framework of the New Hybrid Model by Stover (2010) to be used as a mechanism for interpreting metaphors because the construction of this model is characterized by inclusivity, incorporating cognitive linguistic and pragmatic approaches. However, the strength of the New Hybrid Model has been overlooked by researchers because studies applying this theory are still relatively few compared to other meaning interpretation procedures. Moreover, although there are studies that apply the New Hybrid Model to analyse metaphorical data in their research, the process of interpreting metaphorical meanings is seen to be inconsistent with the ideas proposed by Stover (2010). Recognizing this discrepancy, this paper is responsible for discussing metaphor interpretation procedures based on the New Hybrid Model, focusing on the operation of the Triple Processing Model to prove the credibility of this theory. To illustrate its operation, fire metaphor data generated from the Dewan Bahasa dan Pustaka Corpus are utilized as study materials. Discussion of the New Hybrid Model is significant because correct and systematic procedures can assist researchers in processing implied meanings more accurately and clearly. This paper is hoped to serve as a guide for future researchers in interpreting metaphors as various inputs that manifest the excellence of Malay thinking can be empirically highlighted. Keywords: cognitive, fire metaphor, New Hybrid Model, Malay thoughts, interpretation procedure, Hanna Stover Full text: PDF